Pullulanase Type 1-Assisted Modification of Sago (Metroxylon sagu) Starch - Wong, Chen Wai (2009)
Starch is a versatile food ingredient and is widely used in numerous food and industrials applications. Whether in its native form, or modified through chemical substitution or enzyme modification and/ or physical modification, starch is used as a texturizer, gelling agent, thickener, adhesive, and moisture-retainer. Starches also provide an essential carbohydrate energy source and are obtained from roots, tubers, palms, fruits and cereals, all of which possess unique starch chemistries that impact their properties and function as food ingredients. Starch is a mixture of two polysaccharides, the linear molecule of amylose, which consists of polymers of glucose, and amylopectin, a highly branched molecule. Most starches contain between 15%-30% amylose. Since the major characteristics of starches such as viscosity, shear resistance, gelatinization temperature, solubility, gel stability and textures are affected by the amylose to amylopectin ratios, a wider range of amylose content could extend their applications. In the present study, sago starch was used as a starting material to produce a starch with higher linear chain molecules (amylose) content due to the fact that it is an indigenous and is the main carbohydrate source in Malaysia. Physico-chemical properties were characterized including their amylose content. Result showed that the native sago starch contained of 24.9% amylose. Scanning electron microscopic (SEM) analysis of sago starch granules were predominantly oval, round or bean-shaped and the size is ranging from 15 to 60 μm. The enthalpies of gelatinization (ΔHG) and gelatinization transition temperature range (Tc − To) of 6% (w/v) sago starch suspensions based on differential scanning calorimetric analysis were 19.16 ± 0.79 J/g and 73.9 ± 0.10 °C, respectively. The gelatinization temperature for sago starch obtained by Brabender Viscograph was 72.4°C. Gelatinization temperatures are associated with the loss of birefringence characteristic of starch. Rheological analysis demonstrated that sago starch showed high swelling power and solubility. Pullulanase Type 1 (EC.3.2.1.41) was used to generate more amylose chains (linear long-chain dextrin) from sago starch which contains 24.9% amylose. Starch suspensions of 2.0− 15.0% (w/v) sago starch were heated at 100°C for 45 minutes, which after cooling, the gelatinized sago starch were hydrolyzed with 0.1−10.0% (v/dry weight starch) pullulanase (Promozyme 400L, Novozymes A/S, Denmark) for 0−24 hours. The amylose contents of the hydrolysates after spray-drying (180°C), were then compared with the initial amylose content. The surface morphology of the starch granules was observed with a Scanning Electron Microscope (SEM). The effects of gelatinization and non-gelatinization, time of reaction, pretreatment with different strengths of hydrochloric acid prior to enzyme hydrolysis, and starch and enzyme concentrations were also studied. Raw sago starch was found to be resistant to the action of pullulanase, but caused an increase in the amylose (linear long-chain dextrin) content of that sago starch from an initial concentration of 24.9% to 30.0 − 33.2% following gelatinization. The addition of pullulanase to gelatinized sago starch suspensions resulted in a more runny solution, being more runny with longer reaction time. The effect of acid pretreatment on starch, in place of gelatinization of starch, on the ability of pullulanase to hydrolyze the amylopectin of sago starch was examined. Sago starch was pretreated with various concentrations of HCl (0.5− 6.0 M) at 20°C and 40°C for durations of 1−24 hours. Acid pretreatment of the sago starch did not cause greater improvement in the accessibility and susceptibility of pullulanase as the amylose content following pullulanase action did not change significantly. Shrinkage on the surface of the starch granules was observed with SEM. The best condition to maximize the amount of amylose was 5.0% (w/v) sago starch and 2.0% (v/w) enzyme and 12 hours reaction time. A high-performance size-exclusion chromatograph (HPSEC) equipped with a refractive index (RI) detector and a two-separation columns set up was used to determine and investigate the molecular characteristics of native, fractionated amylose and amylopectin from native sago, and enzyme-catalyzed debranched sago starch. Native sago starch showed a bimodal molecular weight distribution, which indicates fractions that corresponded to amylopectin and shorter linear dextrin chain molecules. The weight average molecular weight (Mw) for the fractionated amylose and amylopectin from sago starch were 8.414 × 105 g/mol and 1.359 × 107 g/mol, respectively. The enzyme-modified starch [5.0% sago starch treated with 0.5-5.0% (v/w) pullulanase for 0.5-24 hours] showed a high molecular weight peak corresponding to that of partially debranched-amylopectin (Mw= 2.875 × 105 − 7.410 × 106 g/mol) and long-chain amylose and a lower molecular weight peak corresponding to the shorter chain amylose molecules, possibly generated from amylopectin by pullulanase, indicating increased concentration of amylose content. The peak area of short chain amylose increased with increasing time of debranching and also enzyme concentration. The Mw for the short chain amylose was between 2.978 × 103− 4.520 × 103 g/mol, equivalent to degrees of polymerization (DPn) between 18 − 23 or number-average molecular weight (Mn) of 2.872 × 103− 3.713 × 103 g/mol. The Mw for amylose of the debranched sago starch is smaller as compared to the native sago starch.